Consumers of Fireworks and Pollution in India : Implications for Marketers and State Policy - Kaur, Bhavneet; Kaul, Vijay Kumar (Indian Journal of Marketing, 2018)
Festivals have been celebrated in India across centuries. Religious festivals like Diwali, Dussehra, Eid, Christmas, etc. bear symbolism and are rooted in the mythologies of their respective faiths, and are observed with specific rituals and celebrations. Most of these celebrations customarily use bright lights and firecrackers. The celebration of these festivals has gained gigantic proportions with the passage of time. The enthusiasm of the consumers has risen along with the pollution caused due to these festivities. Promotions by the marketers and fireworks industry further give a buoyancy to this fervour. Metros like Delhi are one of the first few where the pollution level during festivals has acquired dangerous proportions. In 2016, several festivals were concentrated in the month of October. Coincidentally, the AQI of Delhi jumped from the figure of 160 to 389 from September 30, 2016 to November 1, 2016, depicting a huge fall in its air quality. The present paper aimed to explore the use of firecrackers during festivals and analyzed the stakes of three major parties - the consumers, the marketers, and the state. The paper recommended the need for a change in the way festivals are celebrated by changing the perception of the consumers. It also endorsed for a more ethically responsible behaviour on the part of marketers as well as the state to control the ill effects of using firecrackers.